2022
DOI: 10.3390/ijms23052784
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Wheat Heat Shock Factor TaHsfA2e-5D Conferring Heat and Drought Tolerance in Arabidopsis

Abstract: Environmental stresses, especially heat and drought, severely limit plant growth and negatively affect wheat yield and quality worldwide. Heat shock factors (Hsfs) play a central role in regulating plant responses to various stresses. In this study, the wheat heat shock factor gene TaHsfA2e-5D on chromosome 5D was isolated and functionally characterized, with the goal of investigating its role in responses to heat and drought stresses. Gene expression profiling showed that TaHsfA2e-5D was expressed constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Indeed, TaHsfA2-13 was found to exhibit transcriptional activation activity in this study (Figure 3A). Similarly, in a recent study, the AHA motif was found to be important for the transcriptional activity of TaHsfA2e-5D (Bi et al, 2022). Although NLS and NES coexist, TaHsfA2-13 is normally located in the nucleus (Figures 1, 3B), which differs its orthologue from Arabidopsis (Evrard et al, 2013).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Indeed, TaHsfA2-13 was found to exhibit transcriptional activation activity in this study (Figure 3A). Similarly, in a recent study, the AHA motif was found to be important for the transcriptional activity of TaHsfA2e-5D (Bi et al, 2022). Although NLS and NES coexist, TaHsfA2-13 is normally located in the nucleus (Figures 1, 3B), which differs its orthologue from Arabidopsis (Evrard et al, 2013).…”
Section: Discussionsupporting
confidence: 64%
“…After surface disinfection with 0.1% HgCl 2 , wheat seeds were cleaned with sterile water and soaked at room temperature for 12 h. When the germ grew to 1–2 cm, seedlings were transplanted and cultivated in Hoagland nutrient solution under day/night conditions of 16 h/8 h (70–100 μmol m −2 S −1 ), 25°C, and 50–60% relative humidity. The stress treatments were performed as described by previous studies ( Duan et al, 2019 ; Liu et al, 2020 ; Bi et al, 2022 ). Seedlings at the two-leaf and one-heart stage were treated with high temperature (37°C), low temperature (4°C), H 2 O 2 (10 mmol L −1 ), mannitol (15% W/V), NaCl (0.2 mol L −1 ), MeJA (0.1 mmol L −1 ), ABA (0.2 mmol L −1 ) and SA (0.8 mmol L −1 ) for different time, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These HSPs are extremely important for maintaining the structure of proteins. In reaction to abiotic stress, the HSPs are principally in charge of unraveling some folded proteins and preventing protein denaturation [8]. Transcription factors that regulate and provide an adaptive response under drought stress include myeloblastosis, dehydration-responsive element binding, C-repeat binding factor, abscisic acid responsive elements binding factor, ABRE binding, NAM, ATAF1/2, and CUC2 protein-containing proteins (NAC), WRKY, and SNF1-related kinase 2.…”
Section: Introductionmentioning
confidence: 99%
“…ZmHSF08 has been shown to negatively regulate several stress/ABA-responsive genes under salt and drought stress conditions in maize ( Wang et al., 2021 ). The expression of TaHSFA2e-5D is highly upregulated in wheat seedlings by heat, cold, drought, high salinity, and multiple phytohormones ( Bi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%